La contratación de personal y creación de puestos innecesarios por parte de la autoridad nominadora afecta el presupuesto de la institución pública” - Carrión Castro, Briggette de los Ángeles (2020)
The interest to develop the present thesis that he is titling: "THE RECRUITMENT OF PERSONNEL AND CREATION OF UNNECESSARY POSTS BY THE NOMINATING AUTHORITY AFFECTS THE BUDGET OF THE PUBLIC INSTITUTION", arose with the analysis and study of the legal regulations concerning the recruitment of personnel by the modalities of contracts for occasional services and creation of posts, since it is currently observed that there is an exaggerated hiring of personnel in public institutions, since the appointing authority in the exercise of the attribution conferred by the Organic Law of Public Service, despite knowing the provisions governing these types of recruitment through the rule in question, ignores it and carries out unnecessary hiring, this because when studying this legal norm it is observed that the responsibility due is not established for the cases in which the appointing authority as the maximum authority carries out the hiring of personnel in contradiction to the provisions of the Law and affects the budget destined for other purposes in improvement of the institution, being this legal insufficiency the one that causes the problem that I have approached in the present work, which is a problem of public knowledge and of great importance. The Constitution of the Republic of Ecuador is clear in establishing, in Article 226, that State institutions, their agencies, dependencies, public servants and persons acting under a State authority must exercise only the powers and competences attributed to them in this Magna Carta and the law, and they will also have the duty to coordinate their actions to carry out their purposes; In accordance with article 233 of the same legal body, it stipulates that no public servant shall be exempt from liability for the acts performed in the exercise of his or her functions or for omissions, and shall be administratively, civilly, and criminally liable for the management and administration of public funds, goods, or resources. Being that the appointing authority, by omitting the legally established rules for hiring personnel, must have responsibility for the performance of such act as established by the Constitution of the Republic of Ecuador and consequently by establishing the sanction for these acts improper of a good public administration, the good management of resources can be ensured, as well as the equitable remuneration of them in the provision of public service; a matter that if established in other legislations of countries such as Colombia, Paraguay and the Dominican Republic, on which I base my work through comparative law. In the development of this work through the use of various materials, methods and techniques applicable to it, after the corresponding review of literature and thanks to the results obtained from field research, it was possible to discuss the proposed objectives as well as the respective contrasting of hypotheses, reaching conclusions and recommendations, and thus finish with the preparation of a proposal for the reform of the Organic Law on Public Service and the Comprehensive Criminal Code.